2004
DOI: 10.1063/1.1648135
|View full text |Cite
|
Sign up to set email alerts
|

Combined nanogap nanoparticles nanosensor for electrical detection of biomolecular interactions between polypeptides

Abstract: A concept for the electrical detection of a biological interaction is proposed, mainly based on the conductance variation of a nanometer size-gap (typically less than 100 nm) between two planar electrodes. A functionalized surface was used in the vicinity of the gap in order to concentrate the ligand/receptor complex between the electrodes. The chemistry chosen for the immobilization of the ligand on the biosensor surface is compatible with peptide structures. The receptor in solution was labeled with gold par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Although a study on the fluidics on a nanogap was previously carried out (Brinkmann et al, 2006) to support earlier results with a nanogap biosensor (Haguet et al, 2004), only theoretical calculations were presented. In order to visualize the nanogap filling and support the calculation results provided in previous section, three-dimensional simulations were also performed using CFD-ACE+ TM (CFD Research Corporation, Huntsville, Alabama, USA) with the structure shown in the inset of Fig.…”
Section: Numerical Simulations Of the Nanogap Filling Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a study on the fluidics on a nanogap was previously carried out (Brinkmann et al, 2006) to support earlier results with a nanogap biosensor (Haguet et al, 2004), only theoretical calculations were presented. In order to visualize the nanogap filling and support the calculation results provided in previous section, three-dimensional simulations were also performed using CFD-ACE+ TM (CFD Research Corporation, Huntsville, Alabama, USA) with the structure shown in the inset of Fig.…”
Section: Numerical Simulations Of the Nanogap Filling Processmentioning
confidence: 99%
“…Therefore, this feature of Debye-screening-free sensing is another advantage of the nanogap-DGFET, together with moderate sensitivity and large signal change (Im, H. et al, 2007;Gu et al, 2009). In studies of nanogap-based biosensors (Haguet et al, 2004;Yi et al, 2005), it is very important to understand the fluidics in the nanogap (Brinkmann et al, 2006) because most biomolecules are immobilized and coupled inside a nanogap immersed in a water-based solution. In order to examine the fluidic characteristics in the nanogap of nanogap-DGFET devices, theoretical calculations and numerical simulations are performed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Different type of molecules, crystals, DNA, proteins and other nanostructures have been placed in the nanogap electrodes to pursue next generation of nano-devices [2][3][4][5][6][7][8][9][10]. For this purpose, during the last two decades, a lot of efforts have been devoted to develop techniques for obtaining micro-and nanogap electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the combination of top-down and bottom-up approaches has provided a desired configuration, placement of molecules into nanospace, and promising molecular-recognition results. 76,77,[79][80][81][82][83][84][85][86][87][88] Bottom-up fabrication is achieved through the binding, interaction, self-assembly, and self-organization characteristics of molecules and materials as building blocks. 89 Nanogap devices provide a sufficient level of sensitivity, to as few as a single or small number of biomolecules, with direct transduction of biomolecule-specific binding events into electrical signals.…”
Section: Introductionmentioning
confidence: 99%